Characterization of Two Monoclonal Antibodies Against Human Tissue-Type Plasminogen Activator - Schleef, Raymond R; Sinha, Manjula; Loskutoff, David J (Thrombosis and Haemostasis, 1985)
A series of hybridoma clones, each producing monoclonal antibodies to human tissue-type plasminogen activator (t-PA), were prepared from mice by standard procedures. Two of these clones were selected for further study. One HI72A1, produced antibodies that bound to t-PA and strongly inhibited its activity, whereas another, LI72D1, produced antibodies that bound to t-PA but did not affect its activity. The specificity of these antibodies was assessed in immunoabsorption experiments. Both immunoprecipitated 125I-labeled t-PA, and both were specific since only t-PA was recognized in conditioned media collected from Bowes melanoma cells cultured in the presence of 3H-leucine. Neither antibody recognized urokinase. t-PA was desorbed from antibody HI72A1-Sepharose columns with 0.5 M NaCl, consistent with its relatively low association constant (Ka = 9.37 × 107 M-1). In contrast, a strong chaotropic agent (i.e., 2 M KI) was required to elute t-PA from antibody LI72D1 columns (Ka = 2.08 × 109 M-1). This latter high affinity antibody was employed to develop an immunoradiometric assay for t-PA having a sensitivity of 0.5 ng/ml.
Keywords: Plasminogen activators; Monoclonal antibodies; Inhibition; Immunoradiometric assay